Developing and evaluating a solar installation capacity calculator for residential and non-residential buildings - Othman P.N.F.S.; Mohamed H.; Zuhdi A.W.M.; Roslan M.E.B.M. (American Institute of Physics Inc., 2024)
Solar energy is a promising and easily accessible energy source for meeting long-term energy needs like other Renewable Energy (RE) sources. However, solar energy conversion technologies are now challenged with cost and scalability challenges, particularly in Malaysia. Solar energy must be harvested and stored in a cost-effective manner for it to become a commonly utilized energy source in the country. This project aims to develop a simulator that can accurately design solar photovoltaic (PV) requirements on residential and non-residential rooftop buildings in Malaysia based on the improvised Solar Usage Rooftop Installation Assessment (SURIA) online platform. Commercial buildings, as well as low and high-rise residential buildings were chosen as the case studies for this project. The simulator has been updated to include 88 and 37 new data points for solar panel and inverter specifications, respectively, giving users more options when choosing a panel database. Using the simulator, several sets of simulations are carried out at various panel specifications, considering parameters such as the number of panels mounted on the roof, the capacity of output power generated, and yearly energy provided by the PV system. Simulation at an improved method of area estimation was introduced, in which multiple ratios of 1:2, 3:4, 6:3, and 8:5 are used to calculate the dimensions of the rooftop. The results reveal that the average variation between different ratios is less than 6%, with high-rise residential building having the largest difference from the 1:1 ratio of 5.26%. The comparison of existing online platforms among HelioScope, Meteonorm, and SURIA is discussed at the end of this thesis for documentation purposes, with Helioscope and Meteonorm focusing on design features and SURIA simulator concentrating on cost calculation and PV system installation features. 2023 AIP Publishing LLC.